Resilience Test: The Interplay of Macro Trends and Troubled Financing in Indonesian Sharia People's Financing Bank - Siregar, Depanan Habib; Rasyid, Arbanur; Gautama, Budi; Nasirin, Wanda Khairun (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2024)
Abstract,The increasing trend of BPRS in Indonesia signifies extensive community funding. However, some provinces faced problematic financing, with NPF exceeding 5%, notably over 10% in certain areas.  Macroeconomic trends impact socio-economic conditions, leading to financial challenges like inflation fluctuations, unstable Rupiah exchange rates, and a significant decline in the BI Rate affecting the competitiveness of Sharia financing against conventional loans. The study aims to analyze the relationship between macroeconomic factors and troubled financing in Indonesian BPRS. Employing Purposive Sampling across 20 provinces with the largest assets from 2019 to 2022, the Panel Granger Causality analysis indicates a connection between the exchange rate and NPF. However, economic growth, inflation, and BI Rate show no association with NPF. This suggests significant exchange rate exposure in the BPRS portfolio, necessitating cautious foreign exchange risk management through hedging, regular currency movement monitoring, and consideration of local currency financing policies. Sharia-compliant hedging via forward agreement contracts aligning with Fatwa DSN-MUI No.96/DSN-MUI/IV/2015, PBI No. 18/2/PBI/2016, and Opini DPS No. 17/26/DPS/XII/2015 on Sharia Hedging Plans should be implemented.